Surgical Correction of Facial Skeletal Deformity of Patients with Thalessemia. (June 2014) - Badri, Amir Ali; Keyhan, Seied Omid; Jalalian, Faranak; Fallahi, Hamid Reza; Asayesh, Mohammad Ali; Khiabani, Kazem
Introduction: Our primary intention is to review the literature that has been published in this field and to report some cases of surgical correction of facial and skeletal deformities in patients with thalassemia. Thalassemia is widespread, and about 5% of the world population is affected. Management of facial and skeletal deformity is a major concern in patients with thalassemia, and numerous surgical approaches have been advocated to correct facial deformities, although the type of treatment remains in dispute. Materials and Methods: We report the cases of 3 specific patients who were treated with uncommon surgical procedures after the hematologic condition was corrected. Results: No signs of relapse or maxillary bony overgrowth have occurred in these patients. No massive bleeding occurred during the procedures, and the patients tolerated the surgical approach very well. Complicated surgical procedures, such as bimaxillary segmental osteotomies with 2 or more pieces have been done in patients who had proper systemic conditions without any complications. Conclusions: Maintaining a hemoglobin level of approximately 10 g/dL decreases the risk of preoperative hemorrhage and complications of anesthesia. A complicated surgical approach and more instability during surgery is expected in patients with higher degree of systemic problems. We found that preoperative facial analysis was important in guiding our surgical planning and would benefit the cosmetic outcome as well. Attention to cardiac dysfunction, osteoporosis, vitamin D deficiency, and type of hemoglobin deficiency must be kept in mind, though more surgical cases must be treated before reaching a definitive conclusion.